Pregunta
Score: \( 1 / 25 \) Penalto 1 off Question If \( C=p-1 \) and \( D=-3 p+1 \), find an expression that equals \( 3 C-D \) in standand form.
Ask by Reese Nunez. in the United States
Feb 04,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( 3C - D = 6p - 4 \)
Solución
To find an expression that equals \( 3C - D \) in standard form, follow these steps:
1. **Given:**
\[
C = p - 1
\]
\[
D = -3p + 1
\]
2. **Calculate \( 3C \):**
\[
3C = 3(p - 1) = 3p - 3
\]
3. **Subtract \( D \) from \( 3C \):**
\[
3C - D = (3p - 3) - (-3p + 1)
\]
\[
3C - D = 3p - 3 + 3p - 1
\]
4. **Combine like terms:**
\[
3C - D = (3p + 3p) + (-3 - 1)
\]
\[
3C - D = 6p - 4
\]
5. **Final Answer in Standard Form:**
\[
6p - 4
\]
**Therefore, the expression \( 3C - D \) in standard form is \( 6p - 4 \).**
Answer: \( 6p - 4 \)
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Beyond the Answer
First, let's substitute the values of \( C \) and \( D \) into the expression \( 3C - D \): Substituting \( C = p - 1 \) and \( D = -3p + 1 \) gives: \[ 3C = 3(p - 1) = 3p - 3 \] \[ -D = -(-3p + 1) = 3p - 1 \] Now, combine these results: \[ 3C - D = (3p - 3) + (3p - 1) = 3p - 3 + 3p - 1 = 6p - 4 \] Thus, the expression that equals \( 3C - D \) in standard form is: \[ \boxed{6p - 4} \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium